Evaluación de cuatro tipos de temperaturas con tres distintos tipos de empaque en cultivo de capulí (prunus serotina) en la provincia de Cotopaxi, 2014 - Quispe Sangucho, Luis Alberto (2014)
The research was conducted at Postharvest Laboratory in the Agricultural Engineering Career of Technical University of Cotopaxi, located in the Eloy Alfaro parish, Latacunga Canton, Cotopaxi Province at an altitude about 2920 mamsl. Four room temperatures (environment, 4°C; 6°C; and 8°C) for three types of packaging (Ziploc covers, tubs and Rollpack trays) were evaluated by the researcher. A factorial arrangement 4 x 3 implemented by the researcher was used into a smallholding design with three replications, Tukey method was used for significance testing at 5%. In order to achieve the objectives, the following variables were analyzed: Weight; °Brix; Incidence and severity of illness per days on hanger. According to the results, the researcher concluded: T3 temperature (6°C) was the best as it helps to keep the weight of the fruit, plus get the longest fruit duration into the hanger with 32 days. The packaging e3 (tub) was which presented best features for preservation of the capuli in optimal conditions up to 28 days; and the best interaction was t3e2 (tub + 6°C), as it helps to maintain the health conditions and appropriate weight of capuli in the hanger. So, as recommendation it is advisable to use the t3e2 interaction (tub + 6°C), as it helps to maintain the health and weight of capuli features and perform further research using other type of packaging